2013
DOI: 10.1371/journal.pone.0079225
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Driven Ichthyoplankton Drift Model Predicts Growth of Top Predator Young

Abstract: Climate variability influences seabird population dynamics in several ways including access to prey near colonies during the critical chick-rearing period. This study addresses breeding success in a Barents Sea colony of common guillemots Uria aalge where trophic conditions vary according to changes in the northward transport of warm Atlantic Water. A drift model was used to simulate interannual variations in transport of cod Gadus morhua larvae along the Norwegian coast towards their nursery grounds in the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…The physical oceanographic conditions determine both the vertical distribution of the offspring as well as the horizontal dispersal, as described by Myksvoll et al. (). When running the model on an annual basis, an accumulation of particles within a 100 × 100 km box (i.e., the approximate foraging range of common guillemots around Hornøya; Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical oceanographic conditions determine both the vertical distribution of the offspring as well as the horizontal dispersal, as described by Myksvoll et al. (). When running the model on an annual basis, an accumulation of particles within a 100 × 100 km box (i.e., the approximate foraging range of common guillemots around Hornøya; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…) and was used to show the influence of the availability of cod larvae on the size of common guillemot chicks (Myksvoll et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…For seabirds, one of the potential outcomes of climate change is seasonal mismatch between peak abundance of prey and critical periods of energy demand, such as chick rearing (e.g. Durant et al 2007, Myksvoll et al 2013, potentially leading to reduced breeding success and, eventually, decreasing populations (e.g. Cairns 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the effects of climate variability on and through the different trophic levels is a major challenge, and one that increases in complexity at successively higher levels of the food web (Myksvoll et al 2013). Seabirds are typically at the top of the marine food web and are the most numerous and visible of marine top predators.…”
Section: Seabirdsmentioning
confidence: 99%
“…Many seabirds are at the top of the food chain (see also Sect. 8.5) and it is important to understand which pathways climate signals follow through the food web to influence the different seabird life-history traits (Sandvik et al 2012;Myksvoll et al 2013). Aebischer et al (1990) reported clear similarities between trends in long-term data series of westerly weather and at four trophic levels in the North Sea: phytoplankton, zooplankton, herring, and black-legged kittiwakes, but the mechanisms behind the similarity were unclear.…”
Section: Examples Of Climate Impacts Across Trophic Levelsmentioning
confidence: 99%